(-8)/(2y-8)=(5/(y+4))-7y+(8/(y^2-16))
(-4)/(y-4)=(5/(y+4))-7y+(8/(y+4)(y-4))
((-4)(y+4))/((y+4)(y-4))=((5(y-4))/(y+4)(y-4))-(7y(y+4)(y-4))/(y+4)(y-4))+(8/(y+4)(y-4))
(-4(y+4))=(5(y-4))-(7y(y+4)(y-4))+8
-4y-16=5y-20-(7y(y^2-16))+8
-4y-16=5y-20-7y^3+112y+8
-4y-16=117y-7y^3-12
-4=(121-7y^2)(y)
None of these choices would be equal to -4
Answer:Are there any options?
Step-by-step explanation:
(-a^3b^2*-a^-2b^-3)^-2/2a^2b^-3
= a^4b^9/2a^8b^4
=b^5/2a^4
so your answer is b^5/2a^4
Answer: 75
Step-by-step explanation:
Multiple all those numbers together and then divide by 3